Single tube amplification and detection of male date palm using polymerase chain reaction and loop-mediated isothermal amplification technique - Noppharat Intha; Nutchanat Phakdee; Ryutaro Tao; Peerasak Chaiprasart (Agriculture and Natural Resources, 2021)
Date palm (Phoenix dactylifera L.) is a dioecious fruit species. Date palm seedlings take about 5 yr until their first flowering, which is too long to wait to identify those plants with pistillate flowers that are inappropriate for commercial production. The objective of this research was to develop a method for sex specification of date palm using polymerase chain reaction (PCR) and loop-mediated isothermal amplification (LAMP) incorporating fluorescence detection. A PCR-fluorescent and LAMP technique incorporating fluorescent dye succeeded in sex identification of date palm. The male tubes emitted fluorescence under ultraviolet light (positive), while the female tubes did not emit fluorescence (negative). The use of fluorescent dye integrated in PCR and LAMP could eliminate the electrophoresis step and thereby markedly shortened the time required for analysis. The techniques were developed from previous research and had high accuracy. These techniques amplified and detected within a single tube, were much faster and used less equipment than existing traditional methods. Furthermore, it could reduce the cost by at least USD 5 per sample.